2014
DOI: 10.1111/papt.12042
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to recruitment in mental health services: Care coordinators' expectations and experience of referring to a psychosis research trial

Abstract: Objective High‐quality research trials are necessary to provide evidence for the effective management of mental health difficulties, but successful recruitment can be challenging. Design This qualitative study examines the perceived barriers and facilitators to referring mental health service users to research trials. Seven care coordinators (n = 7) who facilitated the recruitment of participants to a cognitive behaviour therapy – informed psychosis intervention trial were interviewed. Method Demographic infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
(41 reference statements)
2
42
0
Order By: Relevance
“…Well‐designed randomised controlled trials (RCTs) are considered the “gold standard” in clinical research because they provide high‐quality evidence related to the management of specific conditions, including VLUs . Unfortunately, recruitment issues for participation in the RCTs experienced by health professionals are not uncommon . These issues are related to researchers’ inability to recruit the required number of participants or to retain the recruited participants in the study .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Well‐designed randomised controlled trials (RCTs) are considered the “gold standard” in clinical research because they provide high‐quality evidence related to the management of specific conditions, including VLUs . Unfortunately, recruitment issues for participation in the RCTs experienced by health professionals are not uncommon . These issues are related to researchers’ inability to recruit the required number of participants or to retain the recruited participants in the study .…”
Section: Introductionmentioning
confidence: 99%
“…4 Unfortunately, recruitment issues for participation in the RCTs experienced by health professionals are not uncommon. [5][6][7] These issues are related to researchers' inability to recruit the required number of participants or to retain the recruited participants in the study. 8,9 Findings from a systematic review 10 of discontinued RCTs indicate that 76% of the discontinued RCTs were related to poor recruitment.…”
mentioning
confidence: 99%
“…[1][2][3] The National Institute for Health Research (NIHR) performance report for 2013/2014 showed that only five mental healthcare providers were among the top 100 performing healthcare providers recruiting to clinical research. 4 One potential contributing factor is the marked discrepancy in research funding for mental and physical healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…However, trial staff sometimes seemed able to negotiate this challenge by invoking the trial protocol and reminding staff that determining directly from the service user their willingness (or not) to participate was an important outcome within a feasibility study. Mental health staff ltering what patients ended up being approached for recruitment was a key theme identi ed in previous research exploring barriers to recruitment to non-digital psychosis studies (62). Excluding participants for reasons not contained in the protocol likely has implications for the replicability and robustness of research ndings because the selection criteria are obscured (61) and samples likely become biased.…”
Section: Discussionmentioning
confidence: 99%